Analisis Zakat Core Principle dalam Pengelolaan Dana Zakat, Infaq dan Sedekah (ZIS) di Lazismu Bangkalan - Luluk Hanifah; Muhammad Adnan (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Zakat Core Principles (ZCP) are zakat management principles consisting of 18 principles which are grouped into 6 (six) main dimensions of zakat management. These six dimensions are legal basis, zakat supervision, zakat governance, intermediation function, risk management, and sharia conformity. The aim of this research is to review, analyze and find out how the management of the LAZISMU Bangkalan Institution applies the principles of zakat core principles (ZCP). This research uses qualitative methods with primary and secondary data sources related to the Zakat Core Principle analysis in managing zakat, infaq and alms funds. From the research results, several LAZISMU Bangkalan have successfully implemented the Zakat Core Principles (ZCP) in managing ZIS funds. Principles such as transparency, accountability, efficiency and effectiveness have been implemented well, but the principles of transparency are still not optimal in publication, such as access to financial reports is still lacking.